Zsarnay Lajos teológiája - BÁTORINÉ MISÁK, Marianna (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
The Theology of Lajos Zsarnay. Zsarnay’s theological thinking was eclectic. Even though he considered supranatu-ralism the only valid direction, still the interpretations of several doctrines bear the theology and formulation of Schleiermacher. He made it obvious that the views of rationalism are far from his views, and still, according to some suppositions, its doc-trines can be found also in his formulations. He was not familiar with the Hungari-an line of the theological liberalism, but it doesn’t mean that the German liberal thinking did not reach him. But according to our convictions, these views were far from him. He was looking for his own path, while he was open, but also critical to-wards the theological thinking of his time.